Potato cv. Romano reaction to primary and secondary infection with potato necrotic strain Y virus (PVYNTN) - Milošević, Drago M; Ristić, Danijela; Kuzmanović, Slobodan; Starović, Mira (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Primary and secondary infections with PVYNTN were investigated on forty plants of the potato cv. Romano inoculated in a greenhouse in Serbia in 2012 and 2013. PVY isolates were collected from the potato growing region of Čačak and identified by ELISA and RT-PCR methods. The sequence of the Serbian isolate 3D (Acc. No. KJ946936) showed 100% match with seven PVY isolates deposited in GenBank and described as NTN. A significant difference was detected between PVYNTN symptoms exibited on leaves of the cv. Romano under primary and secondary infections. The findings are significant because they are based on symptoms observed, so that it is clear that there are two distinct types of infection: primary and secondary. Symptoms of primary and secondary infection were the same on potato tubers and had the form of necrotic rings.